The Influence Of Organizational Culture And Competence On Performance Of Employees Of Damri State-Owned Enterprises, Lampung Branch - Yovitra, Yovitra; Mahathir Muhammad; Defia Riski Anggarini (Jurnal Ekonomi, 2024)
This study looks at how employee performance at the Perum Damri Lampung Branch is affected by organizational culture and competency. Non-probability purposive sampling is used in this quantitative study, and 126 employees at a 5% margin of error is the sample size determined by the Slovin formula. The study was carried out between September and October, and data was gathered by means of a questionnaire that was given to participants. IBM SPSS Statistics version 27 was used for multiple linear regression data analysis. The results show that: (1) employee performance is positively and significantly impacted by organizational culture; (2) employee performance is positively and significantly impacted by competence; and (3) the Perum Damri Lampung Branch's employee performance is positively and significantly impacted by both organizational culture and competence.